Life and Wisdom in Tembang Lir ilir and Kidung Rumekso ing Wengi: A Philosophical Analysis - Bagaskara, Akbar; Rokhani, Umilia; Kustap (Mudra Jurnal Seni Budaya, 2024)
The traditional Javanese songs created by Sunan Kalijaga, especially Lir ilir and Kidung Rumekso ing Wengi, have tremendous philosophical depth when associated with Javanese culture. Therefore, this research aims to explore and analyze the philosophical meaning contained in the two previous songs and find out how the spiritual messages in these songs are still relevant to the state of society in the modern era. This research uses Ferdinand de Saussure's semiotic analysis to find out the deeper meaning of the text, not forgetting to also use the cultural context approach, to minimize irrelevant interpretations. For data validation, this research uses the triangulation method, where the data comes from interviews, historical records, and direct observation. In practice, the point is to explore the messages contained in the two songs, which are all sourced from the lyrics of these songs and the opinions of experts. The results show that both songs contain philosophical teachings on how to achieve wisdom and peace in every episode of human life. They also teach about the importance of establishing a good relationship with God. In addition, this study also revealed that the spiritual messages in these two songs are still relevant as a reflection of the spiritual journey of everyone in the modern era.